Preparation and Quality Evaluation of Ready to Serve (RTS) Wheatgrass Juice - Adhikari, Babita; Joshi, Sanil (Dristikon: A Multidisciplinary Journal, 2023)
Wheatgrass is an inexpensive and efficient source to provide all the required nutrients and medicinal benefits for a healthy body. The major objective of this study is to formulate a health-beneficial beverage that could be organoleptically accepted by people of all age groups, to bring forward a new product from wheatgrass that has mostly remained unexplored. The wheatgrass harvested on the 9th day (optimized on the basis of chlorophyll, tannin, total polyphenols, flavonoids and DPPH radical scavenging activity) was taken for study. The wheat seeds (WK 1204 variety), collected from Agriculture Botany Division, Nepal Agriculture Research Council were used for the preparation of ready-to-serve juice. Eight different formulations of RTS were prepared with the help of Design-Expert®, version 7, keeping juice content 7-13%, TSS 9-16 °Bx and constant acidity at 0.3%. Response Surface Methodology, D-optimal design was adapted for the formulations. The optimization of the formulation was intended to be carried out based on sensory analysis. Proximate and phytochemical (Chlorophyll, Polyphenol, Flavonoids, Tannins and Antioxidant properties) composition of 9th days harvested wheatgrass, its extracted juice and the final product was also carried out. The statistical analysis (two-way ANOVA, no blocking) was done in order to evaluate the outcomes of sensory analysis. There was a significant difference for sensory attributes like flavor, taste, body and overall acceptability at p<0.05, whereas color wasn’t found to be significantly different. Sensory analysis revealed that the beverage consisting of 12.8% Wheatgrass juice, 12.5°Bx TSS and 0.3% acidity was considered best among all the combinations.